Suspended matter from METEOR cruise M76/2 in the Benguela Upwelling System off Namibia in May 2008 - Emeis, Kay-Christian (Institute for Geology, Biogeochemistry, University of Hamburg, 2025)
Samples were taken with a CTD/Rosette sampler to analyse suspended particulate matter (SPM) and its composition at different water depths. The water samples were filtered using a filtration system consisting of five simultaneous filtration devices, two water pumps and a waste container. Suspended material was collected on pre-weighted and pre-combusted GF/F-filters (ø 47 mm) and dried in an oven at 40°C for at least two days. The total amount of material in each sample was estimated using the volume of water filtered and final weight of dried material. Total particulate nitrogen (TPN), total carbon (TC), particulate organic carbon (POC) were quantified by elemental analysis (Thermo Flash EA 1112). Homogenized samples were weighed into silver capsules and inorganic carbon was removed by adding 1 M HCl suprapur prior to analyses. All data are given in weight%. The method for stable N- isotope composition of TPN is described in Nagel et al., 2013.